The effect of forest management and plant dominant on nitrogen transformation in soils of acidified mountain spruce forests in the Bohemian Forest National Park - Staňková, Pavla (Jihočeská univerzita, 2014)
Cílem práce bylo srovnat množství minerálního a mikrobiálního dusíku pod mrtvým dřevem a čtyřmi rostlinnými dominantami v půdách horských smrčin v oblasti Březníku, NP Šumava. Studované plochy byly napadeny kůrovcem a následně asanovány či ponechány samovolnému vývoji. Diplomová práce hodnotí vliv dominanty a lesnického zásahu na množství a přeměny forem dusíku v půdě.
The effect of forest management and plant dominant on nitrogen transformation in soils of acidified mountain spruce forests in the Bohemian Forest National Park
Keywords: nitrogen; mountain spruce forests; the Bohemian Forest National Park; plant dominant; forest management; transformations; clear-cutting; non-intervention; bark beetle; dead wood; microbial biomass; carbon